2013
DOI: 10.1080/21670811.2013.801690
|View full text |Cite
|
Sign up to set email alerts
|

Al Jazeera English Online

Abstract: AL JAZEERA ENGLISH ONLINE Understanding Web metrics and news production when a quantified audience is not a commodified audience Nikki UsherAl Jazeera English is the Arab world's largest purveyor of English language news to an international audience. This article provides an in-depth examination of how its website employs Web metrics for tracking and understanding audience behavior. The Al Jazeera Network remains sheltered from the general economic concerns around the news industry, providing a unique setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 23 publications
1
25
0
4
Order By: Relevance
“…Also, its use might vary if media organizations are online-only or coexist with other distributions (e.g., print/broadcast channel). All the above are in agreement with prior studies where SEO strategy was found to be varied among newsrooms and factors, such as market orientation, or the ownership/business model were proved to play an important role on how new technologies are incorporated into the journalism profession [6,53,[64][65][66][67]. In short, it may be concluded that news organizations tend to develop distinct forms of SEO use aligned with their organizational imperatives, structures, business model, as well as their editorial priorities.…”
Section: Awareness and Usage Of Seo (Rq1)supporting
confidence: 90%
“…Also, its use might vary if media organizations are online-only or coexist with other distributions (e.g., print/broadcast channel). All the above are in agreement with prior studies where SEO strategy was found to be varied among newsrooms and factors, such as market orientation, or the ownership/business model were proved to play an important role on how new technologies are incorporated into the journalism profession [6,53,[64][65][66][67]. In short, it may be concluded that news organizations tend to develop distinct forms of SEO use aligned with their organizational imperatives, structures, business model, as well as their editorial priorities.…”
Section: Awareness and Usage Of Seo (Rq1)supporting
confidence: 90%
“…Scholars have also observed that newsworkers may ascribe a variety of meanings to audience analytics and the metrics they produce (Hanusch, 2017; Tandoc and Thomas, 2015). For example, Bunce (2019) found that newsroom directors publicly praised and criticized journalists based on readership rates, while Usher (2013) observed that editors at Al-Jazeera English actively sought to minimize the availability and use of metrics. Moreover, according to Powers (2018), the idea of impact is important to today’s newsworkers, but there is little agreement on how to measure it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, journalists still tend to reject audience feedback even in the era of web analytics (MacGregor, 2007;Singer, 2011;Usher, 2013). This is a continuation of the pattern observed in newsrooms long before the onset of online news: journalists had ignored, if not rejected, audience feedback (Gans, 1979;Schlesinger, 1978).…”
Section: Web Analyticsmentioning
confidence: 88%
“…Most newsrooms in the US now use web analytics to monitor audience metrics (Anderson, 2011a(Anderson, , 2011bDick, 2011;Lee et al, 2012;Lowrey & Woo, 2010;MacGregor, 2007;McKenzie, Lowrey, Hays, Chung, & Woo, 2011;Tandoc, 2014b;Usher, 2013). An examination of most news sites will reveal some form of most viewed or most popular stories list (Lee et al, 2012;Thorson, 2008) while a survey three years ago found that 62.1% of editors track web analytics daily (Lowrey & Woo, 2010).…”
Section: Web Analyticsmentioning
confidence: 99%